Pola Resistensi Karbapenem di Rumah Sakit Umum Daerah Kota Mataram - Rifky Arafahtul huda; Mutia Cenderadewi; Rohani Rohani (Malahayati Nursing Journal, 2026)
ABSTRACT Carbapenems are critical last-resort antibiotics for multidrug-resistant Gram-negative infections. Rising resistance threatens patient outcomes and health system resilience, particularly in low- and middle-income countries (LMICs) with limited surveillance and stewardship. This study assessed carbapenem resistance patterns at H. Moh. Ruslan Regional Public Hospital, Mataram, Indonesia. This study aims to describe cases of carbapenem antibiotic resistance in a public hospital in Mataram. Method a retrospective cross-sectional study analysed microbiology laboratory records from January 2023 to December 2024. Bacterial isolates from blood, urine, sputum, pus, and other specimens underwent disk diffusion susceptibility testing. Resistance rates were compared between years. Result a total of 2,478 isolates were analyzed (2023: n = 1,163; 2024: n = 1,315). Overall carbapenem resistance increased from 12.4% in 2023 to 14.1% in 2024. The highest resistance was observed in Acinetobacter sp. (25.7% to 34.3%), followed by Pseudomonas aeruginosa (17.4% to 18.4%), Klebsiella pneumoniae (8.4% to 9.3%), and Escherichia coli (4.7% to 6.0%). Conclusion increasing carbapenem resistance among key Gram-negative pathogens calls for urgent action to reinforce antimicrobial stewardship, guide empirical therapy, and strengthen infection prevention and control. Sustained local surveillance will be essential to preserve carbapenems as vital last-resort agents. Keywords: Antibiotic Susceptibility, Antimicrobial Resistance, Carbapenem Resistance, Indonesia.  ABSTRAK Karbapenem adalah antibiotik terakhir yang kritis untuk infeksi Gram-negatif yang resisten terhadap banyak obat. Meningkatnya resistensi mengancam hasil pengobatan pasien dan ketahanan sistem kesehatan, terutama di negara-negara berpendapatan rendah dan menengah (NBRM) dengan pengawasan dan pengelolaan antibiotik yang terbatas.Studi ini menilai pola resistensi karbapenem di Rumah Sakit Umum Daerah H. Moh. Ruslan, Mataram, Indonesia. Studi ini bertujuan untuk menggambarkan kasus resistensi antibiotik karbapenem di rumah sakit umum di Mataram. Studi potong lintang retrospektif menganalisis catatan laboratorium mikrobiologi dari Januari 2023 hingga Desember 2024. Isolat bakteri dari darah, urine, dahak, nanah, dan spesimen lain menjalani uji sensitivitas difusi disk. Tingkat resistensi dibandingkan antar tahun. Total 2.478 isolat dianalisis (2023: n = 1.163; 2024: n = 1.315). Resistensi karbapenem secara keseluruhan meningkat dari 12,4% pada 2023 menjadi 14,1% pada 2024. Resistensi tertinggi teramati pada Acinetobacter sp. (25,7% menjadi 34,3%), diikuti oleh Pseudomonas aeruginosa (17,4% menjadi 18,4%), Klebsiella pneumoniae (8,4% menjadi 9,3%), dan Escherichia coli (4,7% menjadi 6,0%). Peningkatan resistensi karbapenem di antara patogen Gram-negatif utama menuntut tindakan segera untuk memperkuat pengelolaan antimikroba, mengarahkan terapi empiris, dan memperkuat pencegahan dan pengendalian infeksi. Pemantauan lokal yang berkelanjutan akan menjadi kunci untuk menjaga karbapenem sebagai agen terakhir yang vital. Kata Kunci: Resistensi Karbapenem, Kepekaan Antibiotik, Resistensi Antimikroba, Indonesia.